1995
DOI: 10.1016/0092-8674(95)90165-5
|View full text |Cite
|
Sign up to set email alerts
|

Small peptides activate the latent sequence-specific DNA binding function of p53

Abstract: Normal cells contain p53 protein in a latent state that can be activated for sequence-specific transcription by low levels of UV radiation without an increase in protein levels. Microinjection of cells with an antibody specific to the C-terminal negative regulatory domain can activate the function of p53 as a specific transcription factor in the absence of irradiation damage, suggesting that posttranslational modification of a negative regulatory domain in vivo is a rate-limiting step for p53 activation. Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
319
1
6

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 433 publications
(335 citation statements)
references
References 27 publications
9
319
1
6
Order By: Relevance
“…45 The central role of p53 in preventing malignant transformation makes this gene an obvious target for use in cancer gene therapy. The observation that overexpression of wtp53 could lead tumor cells that have lost wtp53 function either to enter apoptosis or undergo cell cycle arrest 46,47 has stimulated various attempts to restore p53 function by re-expressing the wtp53 gene in tumor cells 47,48 or by introducing peptides which mimic the interaction between p53 and a C-terminal antibody, 49 resulting in a restoration of wtp53 conformation and function.…”
Section: Discussionmentioning
confidence: 99%
“…45 The central role of p53 in preventing malignant transformation makes this gene an obvious target for use in cancer gene therapy. The observation that overexpression of wtp53 could lead tumor cells that have lost wtp53 function either to enter apoptosis or undergo cell cycle arrest 46,47 has stimulated various attempts to restore p53 function by re-expressing the wtp53 gene in tumor cells 47,48 or by introducing peptides which mimic the interaction between p53 and a C-terminal antibody, 49 resulting in a restoration of wtp53 conformation and function.…”
Section: Discussionmentioning
confidence: 99%
“…This activity was shown to be activated by various pathways: phosphorylation (Hupp et al, 1992), antibody speci®c for the carboxyterminus of the protein (Hupp et al, 1992), small peptides which could mimic the carboxy-terminus of the p53 (Hupp et al, 1995), short single stranded DNA (Jayaraman and Prives, 1995), deletion of the last 30 amino-acids (Hupp et al, 1992) and the interaction with a cellular protein (Jayaraman et al, 1997). In the present study, we demonstrate that this feature is not unique to Hp53, but can also be extended to Xp53.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the sequence speci®c DNA binding activity of Xp53 by synthetic peptides Small peptides derived from the carboxy-terminus of Hp53 can activate the latent sequence speci®c DNA binding activity of p53, suggesting an allosteric model for activation of Hp53 (Hupp et al, 1995). Using a series of peptides derived either from Hp53 or Xp53, we examined activation of speci®c DNA binding activity.…”
Section: Xp53 Binding To Human P53 Targets and Can Be Activated By Camentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibition can be relieved by partial proteolysis, DnaK association and by the action of some anti-p53 monoclonal antibodies (Hupp et al, 1992(Hupp et al, , 1993Halazonetis and Kandil, 1993;Hupp and Lane, 1994;Bayle et al, 1995;Waterman et al, 1995). Thus, the monoclonal antibody (mAb) PAb421 (Harlow et al, 1981) is able to increase the sequencespeci®c DNA binding of wt p53 and to restore the sequence-speci®c DNA binding of some p53 mutants in vitro (Hupp et al, 1992(Hupp et al, , 1995Halazonetis and Kandil, 1993;Niewolik et al, 1995, Abarzua et al, 1996. Furthermore, microinjection experiments in tumour cells which express the endogeneous p53 mutant His273 have demonstrated that mAb PAb421 is also able to restore the transcriptional activity of this mutant in cells (Abarzua et al, 1995).…”
mentioning
confidence: 99%